Fatty acid and tocochromanol patterns of some Salvia L. species - Bagci, E; Vural, M; Dirmenci, T; Bruehl, L; Aitzetmüller, K (Verlag Z Naturforsch, 2004)
In the course of our investigations of new sources of higher plant lipids, seed fatty acid compositions and the tocochromanol contents of Salvia bracteata, S. euphratica var. euphratica, S. aucherii var. canascens, S. cryptantha, S. staminea, S. limbata, S. virgata, S. hypargeia, S. halophylla, S. syriaca and S. cilicica were investigated using GLC and HPLC systems. Some of the species are endemic to Turkey. All the Salvia sp. showed the same pattern of fatty acids. Linoleic, linolenic and oleic acid were found as the abundant components. Tocochromanol derivatives of the seed oil showed differences between Salvia species. gamma-Tocopherol was the abundant component in most of the seed oils except of S. cilicica. The total tocopherol contents of the seed oils were determined to be more than the total of tocotrienols.
Keywords: Salvia; chemotaxonomy; fatty acids and tocochromanols